Clinical researchCo-administration of ezetimibe and a statin in management of dyslipidemias: a meta-analysis of clinical trials - Angelopoulos, John; Krassakopoulos, Nickolaos; Nathanson, Robin; Boukas, Stella; Sampalis, John S. (Archives of Medical Science, 2009)
Introduction: Patients, who have above-target low-density lipoprotein cholesterol (LDL-C) levels, are at increased risk for developing coronary heart disease and cardiovascular disease. Statin monotherapy, which decreases the production of exogenous cholesterol, might not be enough to decrease LDL-C levels. Coadministration of a cholesterol absorption inhibitor with a statin may be more effective at decreasing serum LDL-C levels and improving overall lipid profiles. To assess the effectiveness of ezetimibe 10 mg/day coadministered with a statin in reducing serum LDL-C levels. Material and methods: A literature search on PubMed and MEDLINE identified 757 potentially eligible publications of which fifteen reports of clinical trials were qualified to be included in the current review. Results: A total of 5,489 patients included in the studies reviewed were on statin monotherapy prior to study entry for a minimum of 6 weeks. In these studies, the 3,376 patients that received ezetimibe coadministered with a statin had an overall mean percent LDL-C change from baseline of –27.1% (95% CI –27.9 to –26.4%). For the 2,113 that were treated with statin monotherapy the mean change in LDL-C from baseline was –4.5% (95% CI –5.3 to –3.8%). A total of 6,209 patients were treatment-naI¨ve or washed out from any lipid lowering treatment prior to study entry. Of these, the 3,413 that were treated with a combination of statin and ezetimibe combination regimen had an overall mean percent change in LDL-C of –51.5% (95% CI –51.9 to –51.1%). The 2,796 that were treated with statin monotherapy experienced a mean percent change in LDL-C of –40.4% (95% CI –40.9 to –40.0%). Conclusions: Ezetimibe coadministered with statins is effective in reducing LDL-C in patients who do not attain target LDL-C levels while on statin monotherapy. Simultaneous administration of a statin plus ezetimibe regimen in patients who are treatment-naI¨ve is also efficient at reducing plasma LDL-C.